A mechanical tuning method for superconducting filter in both frequency domain and time domain. Issue 1 (25th November 2013) - Song, Xiaoke; Wei, Bin; Cao, Bisong; Guo, Xubo; Zhang, Xiaoping; Zheng, Tianning; Wang, Jingchen; Shang, Zhaojiang
ABSTRACT This article presents a mechanical tuning method for high‐temperature superconducting (HTS) filter based on the frequency domain and the time domain using dielectric tuning rods and metallic tuning rods. The resonant frequency tuning effect with dielectric and metallic rods was analyzed using lumped‐element models. The simulation results showed that the resonant frequency of each resonator can be tuned separately. An eight‐pole HTS twin spiral filter was tuned with the proposed method in frequency domain and time domain simultaneously, as a demonstration. After tuning, the filter has a 16.82 dB return loss, a 0.26 dB insertion loss and a 0.14 dB in‐band ripple. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:217–223, 2014